PERANCANGAN DAN PENGEMBANGAN TERMINAL PENUMPANG BANDARA INTERNASIONAL RADIN INTEN II LAMPUNG - Galih Saprilantu; Tri Yuni Iswati; Amin Sumadyo (ARSITEKTURA, 2016)
Lampung Province area development that keeps increasing every year, in tune with new anyway that is the industrial sector and increasing tourism anyway. Liquid air transport one of the factors that play a role in developing regional Lampung, in addition it also in modern air transport become main options as a means of access to this provincial entry exit. Lampung Province local Government planned to maximize the group by doing airport development Radin Inten II airport into an international class that can accomodate superbly will access inward or outward in the sphere of Indonesia (SNI) and internationally. Development and design of the airport focused more to the passenger terminal, without neglecting other support facilities. Design question is how petite and mass terminal developed concept able to accommodate the predicted flight activities will grow each year, as well as the Lampung Province local wisdom impressions that will be highlighted. This method is used in the design and development is the method of architecture, so that the results obtained are supporting facilities that comply with the standard of the airport that simply playing on international flights, as well as the development of the area of the terminal in order to maximize undertakes activities in it. Keywords: Development, Passanger Terminal, International Airport, Radin Inten II, Lampung Province.